The FENDRR/FOXC2 Axis Contributes to Multidrug Resistance in Gastric Cancer and Correlates With Poor Prognosis - Liu, Hao; Zhang, Zhe; Han, Yanan; Fan, Ahui; Liu, Haiming; Zhang, Xiangyuan; Liu, Yanhong; Zhang, Rugang; Liu, Wanning; Lu, Yuanyuan; Fan, Daiming; Zhao, Xiaodi; et al. (Frontiers in Oncology, 2021)
The dysregulation of long noncoding RNAs (lncRNAs) and transcription factors (TFs) is closely related to the development and progression of drug resistance in cancer chemotherapy. However, their regulatory interactions in the multidrug resistance (MDR) of gastric cancer (GC) has largely remained unknown. In this study, we report a novel oncogenic role of lncRNA FENDRR in conferring MDR in GC by coordinated regulation of FOXC2 expression at the transcriptional and posttranscriptional levels. In vitro and in vivo experiments demonstrated that downregulation of FENDRR expression remarkably decreased drug resistant ability of GC MDR cells while upregulation of FENDRR expression produced the opposite effect. FENDRR overexpression was observed in MDR GC cell lines, patient-derived xenografts and clinical samples. And the high levels of FENDRR expression were correlated with poor prognosis in GC patients. Regarding the mechanism, FENDRR was revealed to increase proto-oncogene FOXC2 transcription by performing an enhancer-like role in the nucleus and by sponging miR-4700-3p in the cytoplasm. Both FOXC2 and miR-4700-3p were shown to be functionally involved in the FENDRR-induced chemoresistance. In addition, there is a positive correlation between FENDRR and FOXC2 expression in clinic and the overexpressed FOXC2 indicated a poor prognosis in GC patients. Collectively, our findings provide a new perspective for the lncRNA-TF regulatory interaction involved in MDR, suggesting that targeting the FENDRR/FOXC2 axis may be an effective approach to circumvent GC chemoresistance.